Trends, features and recent research efforts in the field of hybrid electric vehicles. (30th August 2006) - Adly, Amr A.; Zobaa, Ahmed F.; Nolan, Greg J.
Hybrid Electric Vehicles (HEVs) have attracted tremendous attention as a commercially viable alternative to either traditional vehicles or electric vehicles. Successful HEV design requires optimal sizing of its key mechanical and electrical components. Recently, energy management strategies for HEV have been extensively studied. In addition, for a HEV to be as efficient as possible, proper management of its energy elements is required. Several research studies have been focused on the optimal sizing of HEV components. In this case, a fixed control strategy is employed. On the other hand, there are a number of studies on the optimisation of HEV power management strategy to find the optimal control parameters. In this case, the component sizes are fixed. This paper presents an overview on HEVs including trends, features and recent research efforts in this field.